Muslims in France: features of the integrated model - A. V. Veretevskaya (Vestnik MGIMO-Universiteta, 2012)
The article deals with an acute problem of integration of Muslim immigrants and their descendants in France. The author follows the problem throughout its history and analyzes its modern status. The article provides thorough analysis of the French Integration Model. The author concludes with a prospect on its use in the future.